Application Of The Waterfall Method In The Final Project Guidance Realization Information System - Ritzkal; Puspa Putri Amalia; A. Hendri Hendrawan; Freza Riana; Kodarsyah (Jurnal Mantik, 2022)
The thesis guidance process cannot run smoothly and on time if the busyness between lecturers and students causes a lack of suitable time to meet, so this obstacle can make the problems in writing the thesis unable to be solved as soon as possible. In addition, lecturers also find it difficult to monitor their tutored students because there are not a few students who are mentored. The purpose of this research is (a) to build an information system for the realization of the final project by using the waterfall method and (b) to test using a black box. Based on the results and discussion, conclusions can be drawn as follows: (i) Development of an information system for the realization of the final project in the waterfall method using UML design where the design results include System Actors (List Actor), Use Case Diagrams, Activity Diagrams. (ii) System testing using Black Box. The results carried out using black boxes explain that the system created or the module used is running according to what is specified.